Folk taxonomy and use of mushrooms in communities around Ngorongoro and Serengeti National Park, Tanzania - Tibuhwa Donatha (BMC, 2012)
Abstract Background Maasai and Kurya form two main communities around the Serengeti National Park in Tanzania which are mainly pastoralists. Changing climate to excessive drought, have recently forced them to start practicing subsistence farming which is severely affected by wild animals. This study explored status of the folk taxonomy and uses of mushrooms in the two communities as a pave way for possibilities of introducing mushroom cultivation, an alternative crop which is hardly affected by wild animals. Methods Folk taxonomy and use mushrooms by the Kurya and Maasai communities were investigated. Information was collected by face to face interviews with 150 individuals in 6 selected villages. Using descriptive statistics by Statistic Package for the Social Science (SPSS) version 17.0, the demographic characteristics of informants were evaluated and cross relationships with the recorded data were analysed. Results Kurya are mycophilic with 94% of the informants recognizing utilization of the wild mushroom either as foodstuff or as tonics while the Maasai are mycophobic with 99% being unaware of the edibility of mushroom although 28% recognized mushrooms as tonic. For both communities, the knowledge of mushroom utilization and folk taxonomy increased with age of the informants, while it decreases with formal education level of the informants which imply that the basis of knowledge is mainly traditional. Comparing the two communities, the Maasai use mushrooms only for medicinal purposes and never sought them for food while the Kurya were well knowledgeable on the edibility and folk classification especially the Termitomyces species. Characters used in folkal taxonomy included color and size of the basidiomata, shape and size of the pseudorrhiza, habitats and edibility information. A new use of ascospores whereby they anaesthaesia bees during honey harvesting was discovered, and mushroom cultivation was widely welcomed (94.7%) as an alternative crop which is rarely affected by wild animals. Conclusion In order to salvage a noted tremendous decrease of knowledge in mushroom utilization and folk taxonomy from vanishing, there is a need to document it throughout, and incorporate it in lower levels of our education system. Mushroom cultivation may possibly be the best alternative crop for the two communities thus should be advocated for improving livelihood and reduce human wildlife conflicts. The new recorded use of ascospores to anaesthaesia the bees during honey harvesting should be exploited and scaled up for sustainable integrated bee keeping and mushroom farming.